2018
DOI: 10.1111/bjd.15757
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Psoriasis Area and Severity Index, Dermatology Life Quality Index and EuroQol‐5D response of biological treatment in psoriasis: 10 years of real‐world data in the Swedish National Psoriasis Register

Abstract: Summary Background Few studies have analysed the long‐term effects of biological treatment in psoriasis. PsoReg, the Swedish national register for systemic psoriasis treatment, started in 2006 and now includes 10 years of real‐world data on the effectiveness of biological treatment. Objectives To analyse the long‐term real‐world outcome data of patients who are biologically naïve with moderate‐to‐severe psoriasis after switching to biological treatment. Methods An observational study of patients who are biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Moreover, short-term data on biologics are robust, with up to 70.7% of patients achieving more than 90% reduction in PASI and up to 89.7% achieving a PASI 75 response after 12 weeks of treatment dependent on the specific biologic and dose used (31). Regarding the longer-term effects of biologics, a Swedish study found that switching to biologics was associated with a sustained effect at 10 years with a PASI reduction of 82.8%, a DLQI improvement of 85.7%, and an EQ-5D improvement of 11.0% (32). A study conducted on patients with moderate-to-severe psoriasis comparing the effect of biologics with that of systemic, topical, or light treatment found that biologics resulted in an average mean reduction in DLQI of 6.6 at week 24 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, short-term data on biologics are robust, with up to 70.7% of patients achieving more than 90% reduction in PASI and up to 89.7% achieving a PASI 75 response after 12 weeks of treatment dependent on the specific biologic and dose used (31). Regarding the longer-term effects of biologics, a Swedish study found that switching to biologics was associated with a sustained effect at 10 years with a PASI reduction of 82.8%, a DLQI improvement of 85.7%, and an EQ-5D improvement of 11.0% (32). A study conducted on patients with moderate-to-severe psoriasis comparing the effect of biologics with that of systemic, topical, or light treatment found that biologics resulted in an average mean reduction in DLQI of 6.6 at week 24 (33).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, data from the PsoReg registry showed that the median PASI score in bio-na€ ıve patients who switched to biologic therapy changed from 11.6 at baseline to 3 at threeto-five months after switching and this change persisted over the next six-to-nine years. 31 Another recent study showed that adding topical therapy to patients that have not achieved an adequate response with biologic therapies, may help achieve treat-to-target criteria. 32 In the absence of validated, hard biomarker endpoints, such as the haemoglobin-a1c goal in the treatment of diabetes, treatment targets in psoriatic disease are clinical activity goals that both clinicians and patients can use to evaluate treatment efficacy in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the BJD Hjalte et al . report on their observational study of 583 patients from the Swedish National Psoriasis Register (PsoReg).…”
mentioning
confidence: 99%
“…report on their observational study of 583 patients from the Swedish National Psoriasis Register (PsoReg). Patients were followed for up to 9 years, making this one of the longest biological treatment follow‐up databases . Main clinical outcomes included a disease severity measure, Psoriasis Area and Severity Index (PASI), and two HRQoL measures, Dermatology Life Quality Index (DLQI) and EuroQol‐5D (EQ‐5D).…”
mentioning
confidence: 99%
See 1 more Smart Citation